Quality and acceptability of loaf bread from banana-wheat composite flour - Castaneda, Marissa T; Guzman, Matilde P. (1978., 1978)
A study was conducted to determine the effect of combining banana flour with wheat flour in loaf breads. An emulsifier, Sodium Stearoyl Lactylate (SSL) was further added to improve the baked product particularly its volume. A control bread made from whole wheat and all-purpose flours was used as a basis for comparing the samples with banana flour composite bread. Two levels of banana flour were substituted for wheat flours, 25% and 50% on the wheat flour. Results of the objective ans subjective tests indicated that the samples with banana flour were significantly different from the control bread regarding color, texture, flavor and general acceptability. Increased level of banana flour from 25% to 50% showed a corresponding decrease in volume with a distinct bitter aftertaste. Addition of an emulsifier, SSL, caused and improvement in the volume of the bread. The optimum amount of SSL that was added was 0.20% of the total weight of the ingredients. Increased amount of SSL to 0.50% did not show a significant difference in the volume of the bread from the samples containing 0.2%. There was no improvement in the color, flavor and general acceptability with the addition of an emulsifier.
Thesis (BSFT)--University of the Philippines Diliman.
Keywords: Bread; Flour